ANALISIS KEMAMPUAN KOMUNIKASI DAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS MELALUI TUGAS PROBLEM POSING SERTA PENGARUHNYA TERHADAP SELF CONFIDENCE SISWA SMP - Nur Afriani Agustin; Mirayanti Mirayanti; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to determine the level of communication skills and mathematical creative thinking of junior high school students through tests of straight-line equation questions, and analyze the difficulties of students in solving problems in the matter of straight-line equations. The population in the study were all eighth grade students of Pasundan 1 Junior High School 1 Cimahi with a sample of 9 students in class VIII I who were taken using the proportionate stratified random sampling technique that is by taking samples from each strata proportionally randomly with the provisions of each of the 3 high-ability students , 3 students with moderate ability and 3 low-ability students. The research data was collected through a test of mathematical communication skills based on the indicators of 4 essay questions. The results showed students' mathematical communication skills of 34.4% included in the less category, while for creative thinking ability was 41% including sufficient categories. Based on the answer analysis students have been able to identify elements that are known and asked and stated them in mathematical symbols, able to identify the links between elements / data that are known and asked, only students have not been able to complete mathematical models and determine relevant solutions. Based on the results of the average questionnaire shows that students' self-confidence in mathematics learning can be categorized as being. These results are directly proportional to the results of tests of low mathematical communication skills and creative thinking abilities that are categorized sufficient.